Of sodomites and special rights : a critical discourse analysis of the media texts of an antigay lobby group. - Chew, Chang Hui. (2009)
Evangelical Christians are some of the most vocal opponents of the advancement of lesbian, gay, bisexual and transgender (LGBT) rights. Christians conservative lobby groups, such as the Washington-based Family Research Council, lobby for American federal and state laws to be amended in order to proscribe the advancement of rights for LGBT individuals, disseminating their material through both the mainstream media in the United States as well as their own media channels. The reach of these antigay materials is global, influencing homophobic discourses outsider the United States. Using Fairclough’s (1995, 2001, 2003) and Choulliaraki and Fairclough’s (1999) methods of critical discourse analysis, this study seeks to examine the various discursive materials created by the Family Research Council. Materials are examined for the representation of social actors, largely homosexuals and themselves, as well as larger social structures, such as the institutions of marriage and democracy, to identify the ideology and strategies used to achieve political goals. A total of 143 pieces of text, ranging over a period of 4 years were analyzed, including press releases, books, brochures, opinion pieces, academic work, political and religious newsletters and so on. Representations of homosexuals include traditional images of pedophilia, disease and special rights, destroying marriage, family and democracy. In opposition to this, the FRD represents themselves both as victims of homosexuals and as vigilant Christian watchmen and warriors for religion. Subsequently, the Foucauldian queer theory of Sedgwick (1990) and Halperin (1995) was used to inform the discussion of the various paradoxes of these representations, including homosexuality as a choice of versus homosexuality as identity, as well as FRC as victim versus FRC as victors. These contradictions present a series of double binds that seeks to re-impose a social closet onto GLBT individuals. The study then concludes by suggesting possible strategies to disengage from this homophobic discourse, such as media exposure of the paradoxes and having moderate Christian groups engage the discourse.